Grade 4 lateral patellar luxation in a Newfoundland - Piliero, Marlise Yancey (2010)
This clinical report describes the surgical approaches utilized to correct a grade 4 lateral patellar luxation in a 2.5 year old female spayed Newfoundland. While patellar luxation is one of the most common orthopedic disorders encountered in dogs, lateral patellar luxation is less common than medial luxation. In addition, grade 4 luxation generally involves extensive underlying musculoskeletal abnormalities which must be addressed for successful surgical correction. In the current case, multiple surgical procedures were required before a favorable outcome was obtained. In addition to commonly utilized surgical corrective procedures, a lateral opening wedge femoral osteotomy was performed to maintain patellar alignment.